BUILDING DESIGN OF MES BANCHI (MACHINE PRODUCING BANANA CHIP) WITH UTILIZATION OF THERMOCOUPLE “K” TYPE - Ningsih, Raniya Nur; Timur, Hima Nur Widya; Pratama, Bagus Dwi; Khana’fi, Sha’id; Ferdian, Roby (AIBPM Publisher, 2018)
The purpose of this research is to create a Banana Chip Making Machine that is equipped with thermocontrol, so that the temperature of the frying oil is better maintained. Methodology This study designs the Banana Chip Making Machine, where the slicing process uses an eccentric blade system, then enters the frying pan with a controlled cooking temperature. The results of this study produced Banana Chip Making Machine, where during the trial, it was found that the capacity of 4 kg / hour, where 20 minutes for incision and 40 minutes for frying with a frying temperature reached 250 degrees Celsius. The findings of this study found designs and Banana Chip-making Machines with thermocontrol.